Immunotherapy of chimeric antigen receptor NK cells: status and its promising future - Wang, Fang; Huang, Zhaoyuan; Feng, Xiaoming; Shi, Mingxia (Frontiers in Immunology, 2025)
Chimeric antigen receptors (CARs) are genetically engineered fusion proteins composed of extracellular antigen-recognition domains and multiple intracellular signaling domains. Although CAR T-cell immunotherapy has achieved significant advancements in treating hematologic malignancies, its application against solid tumors remains less successful. Key challenges—including production complexities, the scarcity of tumor-specific antigens, and limitations in cell trafficking and tumor infiltration—continue to impede therapeutic efficacy. Natural killer (NK) cells, essential innate immune lymphocytes, play a critical role in targeting malignant cells. Their unique antigen-recognition mechanisms, potent cytotoxicity, and favorable clinical safety profile position CAR NK cells as a promising alternative for targeted cancer therapy, especially for solid tumors. However, the transient persistence of NK cells in vivo and the technical challenges associated with their preparation currently limit the broader clinical adoption of this approach. This review examines the advantages of CAR NK cells immunotherapy and synthesizes current domestic and international research to advance the understanding of CAR NK cells therapeutics.